2017
DOI: 10.1530/joe-16-0405
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal alterations in PCOS and its influence on bone metabolism

Abstract: According to the World Health Organization (WHO) polycystic ovary syndrome (PCOS) occurs in 4-8% of women worldwide. The prevalence of PCOS in Indian adolescents is 12.2% according to the Indian Council of Medical Research (ICMR). The National Institute of Health has documented that it affects approximately 5 million women of reproductive age in the United States. Hormonal imbalance is the characteristic of many women with polycystic ovarian syndrome (PCOS). The influence of various endocrine changes in PCOS w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
88
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(99 citation statements)
references
References 66 publications
5
88
0
6
Order By: Relevance
“…Similarly, in organismal system pathway, osteoclast differentiation and chemokine signaling (hsa04380 and hsa04062 respectively); apoptosis (hsa04210) under cellular processes; PI3K-Akt signaling pathway (hsa04151) under environment information processing; and protein-processing in endoplasmic reticulum (hsa04141) under genetic information processing class were highly enriched. The results are in line with the findings where involvement of cancer(Dumesic & Lobo, 2013), osteoclast differentiation(Krishnan & Muthusami, 2017), apoptosis(Yan et al, 2012) and PI3k -Akt signaling pathway(Li et al, 2017) are found to be in close relationship with PCOS. The anti-PCOS effects of T. purpurea can be directly linked to these proteins through the protein targeting capability of its DPCs.To elucidate the cellular, molecular and biological level effects of T. purpurea, protein targets of this plant were subjected to gene ontology enrichment analysis.…”
supporting
confidence: 91%
“…Similarly, in organismal system pathway, osteoclast differentiation and chemokine signaling (hsa04380 and hsa04062 respectively); apoptosis (hsa04210) under cellular processes; PI3K-Akt signaling pathway (hsa04151) under environment information processing; and protein-processing in endoplasmic reticulum (hsa04141) under genetic information processing class were highly enriched. The results are in line with the findings where involvement of cancer(Dumesic & Lobo, 2013), osteoclast differentiation(Krishnan & Muthusami, 2017), apoptosis(Yan et al, 2012) and PI3k -Akt signaling pathway(Li et al, 2017) are found to be in close relationship with PCOS. The anti-PCOS effects of T. purpurea can be directly linked to these proteins through the protein targeting capability of its DPCs.To elucidate the cellular, molecular and biological level effects of T. purpurea, protein targets of this plant were subjected to gene ontology enrichment analysis.…”
supporting
confidence: 91%
“…The etiological factors for the onset of PCOS include epigenetic modifications, lifestyle, and environmental exposure to xenoestrogens/xenoandrogens. A previous review published from our laboratory revealed the link between various endocrine changes and its relevance to bone function in PCOS [5]. Polycystic ovary morphology (PCOM) is a well-established feature of PCOS-like phenotype, as PCOS is based on ovarian morphological changes associated with increased ovarian volume, ovarian area, hyperandrogenism and anovulation that collectively leading to reprogramming of hypothalamic-pituitary-ovarian axis [4,6].…”
Section: Introductionmentioning
confidence: 99%
“…In healthy women of reproductive age, the pituitary gland secretes the gonadotropins luteinizing hormone (LH) and follicle-stimulating hormone (FSH) in response to pulsatile secretion of gonadotropin releasing hormone (GnRH) (5,6). These GnRH pulses are more frequent in women with PCOS (3,7). This changed secretion pattern causes an imbalance between LH and FSH, and a higher LH/FSH ratio (3,(7)(8)(9)(10)(11), which may contribute to e.g.…”
Section: Introductionmentioning
confidence: 99%
“…These GnRH pulses are more frequent in women with PCOS (3,7). This changed secretion pattern causes an imbalance between LH and FSH, and a higher LH/FSH ratio (3,(7)(8)(9)(10)(11), which may contribute to e.g. hyperandrogenism and disturbances in follicular maturation and ovulation (3,12).…”
Section: Introductionmentioning
confidence: 99%